How Was the Restructuring of Antisemitism Used to Fuel German Nationalism (1871-1890)? - Flora Warshaw (Central Europe)
This essay seeks to explain through textual analysis of speeches and writings of key antisemitic figures of the time, how German nationalists used antisemitism as a unifying force for citizens, who were disappointed with the lack of German cultural homogeneity in the wake of German unification in 1871. Taking a distinct turn from the religious prejudice suffered by many Jews in what became the German Empire, a new form of racialized antisemitism emerged and created a legacy of racialized hatred that was most commonly associated with the Third Reich.